1998
DOI: 10.1046/j.1523-1747.1998.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Recessive x-Linked Ichthyosis: Role of Cholesterol-Sulfate Accumulation in the Barrier Abnormality

Abstract: Cholesterol sulfate is a multifunctional sterol metabolite, produced in large amounts in squamous keratinizing epithelia. Because patients with recessive x-linked ichthyosis display not only a 10-fold increase in cholesterol sulfate, but also a 50% reduction in cholesterol, we assessed here whether cholesterol sulfate accumulation and/or cholesterol deficiency produce abnormal barrier function in recessive x-linked ichthyosis. Patients with recessive x-linked ichthyosis display both an abnormal barrier under b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 45 publications
2
59
0
2
Order By: Relevance
“…X-linked ichthyosis is due to cholesterol sulfate accumulation owing to a deficiency of the arylsulfatase C/cholesterol sulfatase gene (Shapiro et al ., 1978;Kubilus et al ., 1979;Baden et al, 1980). How abnormally high levels of cholesterol sulfate cause barrier dysfunction has not yet been clearly elucidated (Zettersten et al, 1998), although the T G M 1 gene may be involved (Kawabe et al, 1998). Some ichthyoses are the direct result of genetic defects of lipid metabolism, as exemplified by Refsum's disease (phytanic acid accumul-ation owing to phytanoyl-CoA hydroxylase deficiency) (Steinberg et al, 1978;Jansen et al ., 1997), and Sjogren-L a r s s o n 's syndrome (pathological lipid metabolism owing to fatty aldehyde dehydrogenase deficiency (De Laurenzi et al, 1996;De Laurenzi et al, 1997).…”
Section: Weak Mortarmentioning
confidence: 99%
“…X-linked ichthyosis is due to cholesterol sulfate accumulation owing to a deficiency of the arylsulfatase C/cholesterol sulfatase gene (Shapiro et al ., 1978;Kubilus et al ., 1979;Baden et al, 1980). How abnormally high levels of cholesterol sulfate cause barrier dysfunction has not yet been clearly elucidated (Zettersten et al, 1998), although the T G M 1 gene may be involved (Kawabe et al, 1998). Some ichthyoses are the direct result of genetic defects of lipid metabolism, as exemplified by Refsum's disease (phytanic acid accumul-ation owing to phytanoyl-CoA hydroxylase deficiency) (Steinberg et al, 1978;Jansen et al ., 1997), and Sjogren-L a r s s o n 's syndrome (pathological lipid metabolism owing to fatty aldehyde dehydrogenase deficiency (De Laurenzi et al, 1996;De Laurenzi et al, 1997).…”
Section: Weak Mortarmentioning
confidence: 99%
“…It was proposed that since CSO 4 has trypsin and chymotrypsin inhibitory properties in vitro, it might thereby affect breakdown of desmosomes, thus causing retention hyperkeratoses and abnormal scaling (18). The strong charge of its sulfate moiety conferring mild detergent properties to CSO 4 was shown to interfere with spontaneous sheet-formation of epidermal lipids in vivo and thus theorized to affect epidermal barrier function by deranging skin lipid layers, repressing cholesterol synthesis, and replacing cholesterol in the lipid sheets (16). More recently, it was demonstrated that CSO 4 can induce TGase 1 expression in cultured keratinocytes (19), but the connection between excess TGase expression and disease etiology remains unclear.…”
Section: Effect Of Slv Content Of Cso 4 On -Hydroxyceramidementioning
confidence: 99%
“…In a conceptually related argument, CSO 4 was shown to interfere with spontaneous sheet formation of epidermal lipids in vivo, perhaps due to the strong charge of its sulfate moiety conferring detergent properties to CSO 4 . Thus it was theorized that CSO 4 affects epidermal barrier function both by deranging skin lipid layers and by replacing cholesterol in the lipid sheets (16). In another study, it was proposed that since CSO 4 has trypsin and chymotrypsin inhibitory properties in vitro, it might thereby affect breakdown of desmosomes, thus causing retention hyperkeratosis and abnormal scaling (18).…”
mentioning
confidence: 99%
“…Although the CS accumulation seems to be the primary mechanism contributing to the barrier abnormalities in RXLI, the reduced CHOL levels also play an important role, especially in the altered membrane dynamics. Topically administrated CHOL reverses the pathologic effects of excess CS on SC membrane structure, barrier function, and desquamation [4]. Additionally, ichthyotic symptoms can be induced by cholesterol-lowering drugs [5].…”
Section: Introductionmentioning
confidence: 99%